2007
DOI: 10.2334/josnusd.49.229
|View full text |Cite
|
Sign up to set email alerts
|

Keratocystic odontogenic tumor: a 10-year retrospective study of 83 cases in an Iranian population

Abstract: A retrospective analysis was conducted on patients diagnosed with and treated for keratocystic odontogenic tumor (KCOT) at Mashhad School of Dentistry between 1996 and 2006. The patients comprised 44 men and 30 women with a mean age of 27.08 years. Among the total of 83 lesions, 56 (67.5%) occurred in the mandible and 27 (32.5%) in the maxilla. Swelling tended to be the most common complaint (45.8%), while 24.1% of the lesions were diagnosed incidentally. Six patients (8.1%) with a total of 15 lesions had nevo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
3
26

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 32 publications
9
62
3
26
Order By: Relevance
“…As it is associated with an aggressive characteristic, a high recurrence rate, and based on histological findings, the term was changed to KCOT in the WHO classification in 2005 (Barnes et al 2005;Cakur et al 2008). For a long time, total resection was the only treatment option for KCOT (Habibi et al 2007;González-Alva et al 2008;Grasmuck and Nelson 2010), but complete removal of a large KCOT requires an extensive approach. Some surgeons adopt this conservative approach, which is total resection, for KCOT, whereas marsupialization followed by close follow-up has been proposed by other groups (Nakamura et al 2002;Pogrel and Jordan 2004;Maurette et al 2006;Habibi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it is associated with an aggressive characteristic, a high recurrence rate, and based on histological findings, the term was changed to KCOT in the WHO classification in 2005 (Barnes et al 2005;Cakur et al 2008). For a long time, total resection was the only treatment option for KCOT (Habibi et al 2007;González-Alva et al 2008;Grasmuck and Nelson 2010), but complete removal of a large KCOT requires an extensive approach. Some surgeons adopt this conservative approach, which is total resection, for KCOT, whereas marsupialization followed by close follow-up has been proposed by other groups (Nakamura et al 2002;Pogrel and Jordan 2004;Maurette et al 2006;Habibi et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the treatment for KCOT has been total resection and extraction of the cyst-associated tooth (Habibi et al 2007;González-Alva et al 2008;Grasmuck and Nelson 2010). The recurrence rate with total resection varies among reports.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habibi et al study on Iranian populations showed that 8.1% of 83 cases with KCOTs, were associated with NBCCS and 7.6% of them had recurrence [21].…”
Section: Minor Criteria [13-15]mentioning
confidence: 99%
“…The role of mutation of the PTCH gene in the etiology of KCOTs resulted in reclassification of this lesion as a neoplasm in the WHO classification of head and neck tumors in 2005 and its renaming as KCOT (5). KCOTs often occur in the mandibular ramus and angle region but rarely in other mandibular regions and in the maxillary region (7,8). Radiographically, KCOTs present as well defined radiolucent lesions with smooth and usually corticated margins.…”
Section: Introductionmentioning
confidence: 99%